Clinical characteristics of temporomandibular joint involvement in children with juvenile idiopathic arthritis - Kaarto, Maija; Snäll, Johanna; Möttönen, Milja; Suominen, Auli; Hirvonen, Jussi; Thorén, Hanna (Springer Nature, 2026)
Purpose
To describe and compare clinical characteristics of TMJ involvement in a sample of children with oligoarthritis and seronegative polyarthritis, and to identify factors increasing the odds for different types of TMJ involvements.
Methods
A retrospective cross-sectional study of 62 children with oligoarthritis or seronegative polyarthritis and associated clinical TMJ involvement at the age of 15 years or younger (range 2–15, mean 7.9, SD 3.6, median 6.7).
Results
Clinical TMJ involvement was frequently (35 children, 56.5%) diagnosed early (0 to 12 months) after JIA diagnosis. In five children (8.1%), TMJ involvement was identified prior to diagnosis of JIA. Subjective symptoms were far more infrequently reported (30 children, 48.4%) than abnormal clinical findings (57 children, 91.9%). The most common symptom was pain (28 children, 45.2%) and the most common clinical finding was disturbance of mandibular movements (46 children, 74.2%). Mandibular asymmetry was observed in 18 (29.0%) children. No significant differences in TMJ symptoms and clinical findings were observed between children with oligoarthritis and seronegative polyarthritis. MRI findings were absent in 20 (32.3%) of 62 children.
Conclusions
No significant clinical differences between the two JIA groups were observed, likely due to the small sample size. However, important overall characteristics were observed: TMJ involvement frequently presented without any subjective symptoms, and one out of three children had mandibular asymmetry already at the time of diagnosis of TMJ involvement. The findings emphasise the importance of regular examinations of the TMJ in children with JIA in order to prevent facial growth disturbance and malocclusion.